Trust Management as Social Capital in Building Organizational Sustainability - Hilmi Wiranawata (Maneggio, 2026)
This study examines trust management as a form of social capital and its implications for organizational sustainability in increasingly complex and dynamic environments. Trust is recognized as a critical element that shapes stakeholder relationships, enhances collaboration, and supports sustainable performance across environmental, social, and governance (ESG) dimensions. The study aims to develop an integrative framework that explains how trust contributes to sustainability outcomes. A qualitative approach was employed using a systematic literature review and conceptual synthesis of scholarly articles published between 2021 and 2025. Data were collected through document analysis and analyzed using thematic content analysis combined with a systems thinking approach. The findings reveal that trust operates as a multidimensional construct encompassing internal, external, and institutional dimensions, influencing employee engagement, innovation, ESG performance, and organizational resilience. The discussion highlights that trust facilitates knowledge sharing, strengthens governance, supports digital transformation, and enhances collaborative partnerships, thereby contributing to long-term sustainability. In conclusion, trust management serves as a strategic mechanism that enables organizations to navigate uncertainty, improve adaptability, and achieve sustainable performance.